(untitled) (Journal of the College of Basic Education, 2023)
By the end of World War I in 1918 AD, Britain would have emerged victorious from the war, but it was suffering from a very difficult economic and financial crisis, and a tired army that needed rehabilitation. And almost destroyed naval forces, and lost two-thirds of its ships and equipment, and destroyed cities, roads and ruined bridges, and despite that, it had extended its control over its colonies in the Indian subcontinent, the Arabian Gulf, Persia, Iraq, Palestine, Transjordan, Aden, Bab al-Mandab Strait, parts of Somalia, the Red Sea, and Egypt Sudan, Cyprus, Crete, and the Balearic Islands in the Mediterranean Sea, and on large parts of its coasts and islands, and the coasts of the Red Sea, the Gulf of Aden, the Indian Ocean, and the Arabian Gulf (1).